2022
DOI: 10.55446/ije.2022.593
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Vector Borne Disease Transmission: Current Strategies of Mosquito Vector Control

Abstract: .In this review, the mosquito vector borne diseases (VBD) majorly malaria, dengue, filariasis, chikungunya, Japanese encephalitis, Zika were presented to comprehend the global disease incidence as the control of these disease transmitting vectors are challengeable globally nowadays. It has been found that malaria affects nearly 500 million people and lymphatic filariasis about 100 million people worldwide every year. About 25 million people are infected by dengue, with approximately 25,000 deaths annually. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Insecticide resistance in Anopheles mosquitoes, reported since the, 1950s, now threatens malaria control, risking a disease resurgence ( Suh et al., 2023 ). Insecticide resistance is a global concern, affecting over 500 insect species, including over 50 Anopheles species responsible for transmitting malaria to humans ( Manikandan et al., 2022 ). Large-scale efforts, including ITNs, indoor spraying, and improved case management, reduced malaria cases from 81.1 per, 1000 in, 2000 to 58.9 in, 2015 ( Suh et al., 2023 ).…”
Section: Vector Control Methodsmentioning
confidence: 99%
“…Insecticide resistance in Anopheles mosquitoes, reported since the, 1950s, now threatens malaria control, risking a disease resurgence ( Suh et al., 2023 ). Insecticide resistance is a global concern, affecting over 500 insect species, including over 50 Anopheles species responsible for transmitting malaria to humans ( Manikandan et al., 2022 ). Large-scale efforts, including ITNs, indoor spraying, and improved case management, reduced malaria cases from 81.1 per, 1000 in, 2000 to 58.9 in, 2015 ( Suh et al., 2023 ).…”
Section: Vector Control Methodsmentioning
confidence: 99%
“…Anopheles stephensi mosquitoes transmit P. falciparum , which causes chikungunya, dengue, malaria, yellow fever, Zika fever, Japanese encephalitis, and lymphatic filariasis among other awful illnesses, to humans [ 100 ]. Many areas, including industrial, pharmaceutical, and medical, rely on research into the production of bio-metal nanoparticles [ 101 ]. This encompasses both diagnostics and therapies, exhibiting a wide array of in vitro properties such as antibacterial, cytotoxic, and antibiofilm efficacy, as well as impacting inflammatory and coagulation responses.…”
Section: Utilizing Medicinal Herbs For Nanoparticle Synthesismentioning
confidence: 99%
“…Furthermore, pollination by adult dipterans whose larvae develop in aquatic microhabitats is an important ecosystem service (Orford et al 2015) that may be changed in urban space if insect larvae respond to urbanization. On the other hand, tree-hole inhabiting mosquitoes that may bene t from urbanization can act as disease vectors and may threaten human health (Manikandan et al 2022). However, there is not much information on urban aquatic microecosystems such as tree holes, their infauna and their responses to urbanization.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the congeneric species Aedes aeqypti it could be shown that with increasing urbanization their host preference shifted towards humans(Rose et al 2020). Due to the potential of transmitting diseases by several species of the genus Aedes(Manikandan et al 2022), we encourage public information campaigns on the larval development of mosquito species and possible countermeasures such as the prevention of temporary waters in residential areas to avoid further spreads and a potential colonization of further hazardous species such as Aedes albopictus(Manikandan et al 2022;Skinner et al 2023).…”
mentioning
confidence: 99%